DICOTYLEDONOUS PLANTS - Shodiyeva Salomat Abdishukurovna (Journals Park Publishing, 2022)
Plant taxonomy is one of the oldest fields in biology. Of course, this field was created out of necessity. The modern plant system is based on long-term research, observations, and paleobotanir evidence. In this article, we will focus on dicotyledonous plants and their importance, as well as examples in nature.
Keywords: biology; dicotyledonous plants; tulips